How do we choose a partner: Testing some predictions of the evolutionary theory - Tadinac, Meri (Array, 2005)
Hypotheses of evolutionary psychologists concerning the mate choice and sex differences in preferred mate characteristics have been tested in various cultures. The research in this field was strongly influenced by Trivers' theory of parental investment and sexual selection which postulates that due to different selective pressures and adaptive problems posed to men and women, their strategies tended to evolve differently. Women should be choosier than men and exhibit a stronger preference for attributes of ambition, social status and financial wealth in partner, as well as for a desire for children and commitment to family, which are indicative of the partner's ability to acquire and invest the resources necessary for the survival of offspring. Men should exhibit a stronger preference than women for indicators of youthfulness, health and physical attractiveness, which are indicative of high reproductive potential, as well as for indicators of sexual fidelity, which are important because of the high costs for men who are cuckolded. The theory also predicts sex differences in jealousy: women should be more upset by the emotional infidelity of their partners, while men should exibit stronger sexual jealousy. To test the basic assumptions concerning sex differences in mate choice and jealousy we conducted an internet-based study on the broad Croatian sample using a questionnaire based on the well known Buss' instrument. The majority of our subjects were heterosexual, but the sample also included homosexual and bisexual subjects. Our results support the basic assumptions derived from the theory: men seek short-term mates more than women do ; sex differences were found in rankings of desirability of certain characteristics of a potential mate, as well as in his/her preferred age ; more men than women would express sexual vs. emotional jealousy